The Strategic Role of Civil Society Organizations in Disaster Management After the Turkey-Syria Earthquakes 2023 - BOZKURT, Önder; ÇİÇEKDAĞI, Halil İbrahim (Future Science / FSH-PH Publications, 2025)
Following the earthquakes centered in Kahramanmaraş on February 6, 2023, both national and international non-governmental organizations (NGOs) provided significant support and contributions, not only assisting in search and rescue activities but also playing a critical role in emergency humanitarian aid processes. Within the scope of this research article, the activities of both national and international NGOs in pre-disaster preparation, disaster response and post-disaster recovery processes were examined in detail. In the research, 10 nationally recognized NGOs that took part in the February 6 Earthquakes in Türkiye and NGOs with active websites from 10 different European countries were selected, and the websites of these organizations were examined and their activities regarding disaster management processes were evaluated. As a result of the study, it was comparatively revealed how both national and international NGOs integrated into the disaster management system and in which areas they contributed more. The study was concluded with some evaluations and suggestions regarding what needs to be done for NGOs to be more effective and successful in disaster management in the following processes.